Pembinaan dan Pengawasan Pemerintahan di Daerah Manado Dengan Metode Studi Literatur - Darmawan, Ivan; Aisyah, Nur; Aulia, Fayyaza Azwa; O, Olivia (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to examine the implementation of regional government information systems in Manado City with a focus on the Regional Planning, Research and Development Agency (Bapelitbangda). The method used is a literature study which includes analysis of various sources of related information. The research results show that the implementation of regional government information systems has a significant impact on the efficiency and effectiveness of public administration.